Evaluation of Macroalgae Sulfated Polysaccharides on the Leishmania (L.) amazonensis Promastigote - Pires, Camila Lehnhardt [UNESP]; Rodrigues, Selma Dzimidas [UNESP]; Bristot, Daniel [UNESP]; Gaeta, Henrique Hessel [UNESP]; Toyama, Daniela de Oliveira; Lobo Farias, Wladimir Ronald; Toyama, Marcos Hikari [UNESP] (Mdpi Ag, 2013)
The sulfated polysaccharides from Solieria filiformis (Sf), Botryocladia occidentalis (Bo), Caulerpa racemosa (Cr) and Gracilaria caudata (Gc) were extracted and extensively purified. These compounds were then subjected to in vitro assays to evaluate the inhibition of these polysaccharides on the growth of Leishmania (L.) amazonensis promastigotes. Under the same assay conditions, only three of the four sulfated polysaccharides were active against L. amazonensis, and the polysaccharide purified from Cr was the most potent (EC50 value: 34.5 mu g/mL). The polysaccharides derived from Bo and Sf demonstrated moderate anti-leishmanial activity (EC50 values of 63.7 mu g/mL and 137.4 mu g/mL). In addition, we also performed in vitro cytotoxic assays toward peritoneal macrophages and J774 macrophages. For the in vitro cytotoxicity assay employing J774 cells, all of the sulfated polysaccharides decreased cell survival, with CC50 values of 27.3 mu g/mL, 49.3 mu g/mL, 73.2 mu g/mL, and 99.8 mu g/mL for Bo, Cr, Gc, and Sf, respectively. However, none of the sulfated polysaccharides reduced the cell growth rate of the peritoneal macrophages. These results suggest that macroalgae contain compounds with various chemical properties that can control specific pathogens. According to our results, the assayed sulfated polysaccharides were able to modulate the growth rate and cell survival of Leishmania (L.) amazonensis promastigotes in in vitro assays, and these effects involved the interaction of the sulfated polysaccharides on the cell membrane of the parasites.
Keywords: macroalgae; Leishmania (L.) amazonensis; sulfated polysaccharides; Solieria filiformis; Botryocladia occidentalis; Caulerpa racemosa; Gracilaria caudate